2020
DOI: 10.32598/rmm.8.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kohlrabi (Brassica oleracea Var. Gongylodes) Extract Effect on Mesenchymal Stem Cells Viability and Apoptosis

Abstract: Background: Cell viability and apoptosis are two crucial factors that may determine cell fate. There are several factors, such as hypoxia, which may be effective in cell processes. Because of its unique features, such as its antioxidant, anti-inflammatory, and anti-apoptosis mechanisms, kohlrabi (Brassica oleracea var. gongylodes) extract may be used in the amelioration of cell viability and a decrease in cell apoptosis. In this study, we evaluate the effect of kohlrabi extract on the viability and apoptosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Written informed consent was taken from volunteer patients undergoing liposuction surgery to collect adipose tissue samples which are considered surgical waste material. The AD-MSCs were characterized and isolated according to our previous study using the same isolation and culture protocol of AD-MSCs in which cells were confirmed through assessing morphology, surface marker flow cytometry, and triple differentiation ability into chondrocyte, osteocyte, and adipocyte lineages [ 26 ]. Briefly, the adipose tissue samples were mechanically segmented and then rinsed with phosphate-buffered saline (PBS) several times.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was taken from volunteer patients undergoing liposuction surgery to collect adipose tissue samples which are considered surgical waste material. The AD-MSCs were characterized and isolated according to our previous study using the same isolation and culture protocol of AD-MSCs in which cells were confirmed through assessing morphology, surface marker flow cytometry, and triple differentiation ability into chondrocyte, osteocyte, and adipocyte lineages [ 26 ]. Briefly, the adipose tissue samples were mechanically segmented and then rinsed with phosphate-buffered saline (PBS) several times.…”
Section: Methodsmentioning
confidence: 99%